Aceh and Mindanao: A Comparative Study of Postcolonial Muslim Experiences in Democratic States - Huswatun Miswar, Syarifah (Universitas Islam Internasional Indonesia, 2025)
This study offers a comparative analysis of the postcolonial experiences of Muslim communities in Aceh (Indonesia) and Mindanao (Philippines), focusing specifically on the impact of colonialism on institutions, legal structures, and religious identity. Both regions, while sharing a Muslim-majority population and a long history of colonial domination, have developed distinct trajectories in their approaches to governance, law, and cultural identity within contemporary democratic frameworks. Aceh, as a province of Indonesia, implements Islamic Sharia through special autonomy, reflecting a negotiated balance between local religious identity and national legal structures. In contrast, Mindanao continues to face challenges in securing Muslim rights through peace agreements, such as the Bangsamoro Organic Law, highlighting ongoing struggles over institutional autonomy and legal recognition. Employing a comparative approach, this study analyses three main aspects: the legacy of colonial institutions and legal systems, postcolonial transformations in governance and identity, and the dynamics of Muslim political participation in democratic states. The findings demonstrate that colonialism has left a profound imprint on the social, legal, and religious structures of both regions, but their responses have diverged due to differences in cultural contexts, national policies, and local agencies. This study contributes to broader discussions on decolonization and Islamic studies in the Global South by highlighting the diversity of post-colonial Muslim experiences in democratic societies.